FREQUENCY AND FACTORS OF NON-COMPLIANCE AMONG EPILEPTIC PATIENTS - Gilani, Atifa; Nawaz, Khurram Haq; Hassan, Zahid; Yousaf, Muhammad Ali; Hashmat, Asif; Arif, Saeed (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the frequency of non-compliance among the patients of epilepsy and factors related to the presence of non-compliance at a tertiary care hospital of Pakistan.Study Design: Cross-sectional analytical study.Place and Duration of Study: Neurology department, Pak Emirates Military Hospital Rawalpindi, form Dec 2018 to Jun 2019.Methodology: A total of 133 cases were included in the study, which were diagnosed as epilepsy for more than 6 months by a consultant neurologist. Medication and drug adherence was assessed by validated Urdu version of our-item Morisky Medication Adherence Scale. Relationship of age, gender, socio-economic class, duration of epilepsy, education, marital status and poly-pharmacy was assessed with the presence of non-compliance among the patients suffering from epilepsy.Results: There were 53 (39.9%) patients were females while 80 (60.1%) were males. Out of 118 patients of epilepsy, 59 (44.4%) showed the presence of non-compliance while 74 (55.6%) had good compliance. After applying the logistic regression we found that duration of illness and poly-pharmacy had significant association with the presence of non-compliance among the patients of epilepsy.Conclusion: Non-compliance emerged as a highly prevalent behavior or clinical condition among the patients of epilepsy in our target population. Before combining the pharmacological agents it is advisable to check the compliance of already prescribed drugs used to control the seizures. Patients with long standing illness or those who are put on multiple medications should be regularly screened for non-adherence.